Pengembangan Buku Ajar Ekologi Dengan Memanfaatkan Hasil Analisis Potensi Ekosistem Mangrove Sebagai Penyerap Karbon - Ilyas Husain; Abubakar Sidik Katili; Elya Nusantari (Jambura Edu Biosfer Journal, 2019)
Analysis of Mangrove Ecosystem Potential as Carbon Absorbent, For Development of Textbook Material On Ecology Course". Thesis of Graduate Program of State University of Gorontalo (UNG). The principal supervisor was. Prof. Dr. Ramli, Utina, M.Pd. and the co-supervisor was Dr. Elya Nusantari, M.Pd. This study aims To determine the quality of textbooks based on research for the development of teaching materials on the subject of ecology subject matter and energy. Development of research-based learning tools of subject matter and Energy using R D model through 10 steps of development then simplified on three stages, namely (1) exploration stage, (2) prototype development stage, and (3) product validation stage, As for the products produced in this study is a textbook. The resulting product development is then validated by material experts, design experts, and students. The result of the research shows that (1) textbook based on research according to the material expert from the whole aspect of assessment for the validation of textbook is 93.75% including excellent quality, because it is in the range of 81% to 100%, (2) For the validation of textbook design is 91.67%, including excellent quality, because it is in the range of 81% to 100%, (3) student response to the overall quality of textbook aspect is at 94% percentage where this value belongs to very good category because it is In the range of 81 to 100%.